Cold Houses in Warm Climates and Vice Versa: A Paradox of Rational Heating - Friedman, David (Journal of Political Economy, 1987)
Houses in cold climates are kept warmer in winter than those in warm climates, des pite the greater cost of heating in colder climates. It is shown that this is not only consistent with, but also implied by, rationality. The contrary intuition is based on a confusion between average and ma rginal cost. The same analysis implies that it is rational to keep th e thermostat setting constant throughout the heating season rather th an changing it with changes in external temperature. Copyright 1987 by University of Chicago Press.